Hippocampal region metabolites and cognitive impairment in patients with general paresis: based on 1H-proton magnetic resonance spectroscopy - Xin Che; Xin Che; Xin Che; Tianyang Miao; Tianyang Miao; Tianyang Miao; Haishan Shi; Haishan Shi; Haishan Shi; Zezhi Li; Zezhi Li; Zezhi Li; et al. (Frontiers Media S.A., 2024)
Background:This study utilizes Hydrogen proton magnetic resonance spectroscopy (1H-MRS) to investigate metabolite concentrations in the bilateral hippocampus of general paresis (GP) patients.Methods:A total of 80 GP patients and 57 normal controls (NCs) were enrolled. Metabolite ratios in the bilateral hippocampus were measured using 1H-MRS. Cognitive function was assessed using the Mini-Mental State Examination (MMSE). Based on MMSE scores, participants were categorized into normal control, mild cognitive impairment, and moderate-severe dementia groups. Metabolite ratios (N-acetylaspartate (NAA)/creatine (Cr), choline (Cho)/creatine (Cr), N-acetylaspartate (NAA)/choline (Cho), myoinositol (MI)/creatine (Cr), choline (Cho)/N-acetylaspartate (NAA)) were compared between groups, and correlations between metabolite ratios and cognitive performance were examined.Results:MMSE scores progressively decreased in the normal, mild cognitive impairment, and moderate-severe dementia groups (p < 0.001). The moderate-severe dementia group showed significantly lower NAA/Cr ratios in the left hippocampus region (L-NAA/Cr ratios) (p < 0.001) and higher Cho/NAA ratios in the left hippocampus region (L-Cho/NAA ratios) (p < 0.05) compared to the other groups. However, differences in L-NAA/Cr and L-Cho/NAA ratios between the mild cognitive impairment group and the NC group were not significant in the hippocampus region (p > 0.05). NAA/Cho and NAA/Cr ratios in the right hippocampus region (R-NAA/Cho and R-NAA/Cr ratios) in the moderate-severe dementia group were lower than those in the control group (p < 0.05). No correlation was found between metabolite ratios and MMSE scores in bilateral hippocampus regions.Conclusion:There are distinctive metabolic characteristics in the hippocampus of GP patients. GP patients exhibited lower NAA/Cr and NAA/Cho ratios in the bilateral hippocampus, indicating neuron loss in these areas, which may become more pronounced as the disease progresses.